2014
DOI: 10.1074/jbc.m113.450163
|View full text |Cite
|
Sign up to set email alerts
|

Role of Annexin A5 in Cisplatin-induced Toxicity in Renal Cells

Abstract: Background: There is increasing evidence that annexin A5 is related to cytotoxicity, but the precise function has yet to be elucidated. Results: Cisplatin induces mitochondrial translocation of annexin A5, and annexin A5 mediates VDAC oligomerization. Conclusion: Annexin A5 may play a role as a mediator of cisplatin-induced apoptosis in renal epithelial cells. Significance: Learning how annexin A5 is involved in the apoptotic pathway is crucial for understanding cisplatin-induced toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
2
30
1
Order By: Relevance
“…. Research over the past few years has gained significant insights into the mechanisms regarding cisplatin nephrotoxicity, which mainly involved apoptosis, inflammation and oxidative stress et al 171819202122…”
mentioning
confidence: 99%
“…. Research over the past few years has gained significant insights into the mechanisms regarding cisplatin nephrotoxicity, which mainly involved apoptosis, inflammation and oxidative stress et al 171819202122…”
mentioning
confidence: 99%
“…Recently, Jeong et al (2014) and Kwon et al (2013) reported that annexin A5 plays an important role in cisplatin-induced mitochondriadependent apoptosis via oligomerization of VDAC. In the present study, an important role for annexin A5 was further confirmed in mitochondria-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that annexin A5 plays an important role in cisplatininduced mitochondria-dependent apoptosis in renal cells (Jeong et al, 2014;Kwon et al, 2013). To determine whether annexin A5 participated in auranofin-induced mitochondriadependent apoptosis, changes in annexin A5 mRNA and protein expression were measured.…”
Section: Auranofin Induces Expression Of Annexin A5 and Translocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of VDAC3 increases mitochondrial production of the reactive oxygen species, alters renal sodium transport, and leads to hypertension whereas deletion of VDAC2 is lethal during embryonic development [28,29]. Oligomerization of VDAC1 has been implicated in cisplatin-induced apoptosis and nephrotoxicity due to a formation of pores in the outer mitochondrial membrane that allow for the escape of cytochrome c from the mitochondrial intermembrane space to the cytosol [30]. As VDAC1 conductance can differentially mitigate or exacerbate pathological conditions in different organs and cell types, the purpose of this study was to determine the role of VDAC1 in (1) ischemia-induced mitochondrial dysfunction and injury to the kidney, and (2) kidney repair after ischemia.…”
Section: Introductionmentioning
confidence: 99%